ANALISIS FINANSIAL DAN RISIKO INVESTASI TEKNOLOGI PISANG KULTUR JARINGAN DI KABUPATEN LAMPUNG SELATAN - Fadila Marga Saty; Muhammad Irfan Affandi; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aims to evaluate financial banana farming with the technology of tissue culture and plantlets the shoot bananas and analyze investment risk with NPV at risk. The research was carried out in the South Lampung Regency Ketapang Subdistrict, Penegahan, Bakauheni, Kalianda, Raja Basa, Katibung, and Palas. The choice of location because the districts and villages of the farmers receiving the aid program the banana tissue culture seedlings of PUPKP (Program Unggulan Pengembangan Komoditas Pisang). The number of respondents was 40 farmers’ tissue culture and plantlets the shoot farmers 42. To answer the first objective financial analysis, we calculated NVP, IRR, Gross BC, Payback Period and sensitivity, whereas the second purpose was analyzed bycalculating NVP at risk. The results showed that banana farming in South Lampung Regency was financially viable, the value of NPV was Rp11,220,349.21; IRR 32.14percent; Gross BC ratio 1.24 and Payback Period was2 year 7 months for farming of banana tissue culture, while on the farming of banana shoots puppies the value of NPV was Rp25,874,245.92; IRR  98.25percent, Gross BC  1.84 and Payback Period was 1year 7months. Analysis of financial investment risks banana tissue culture seedlings and saplings shoot based on the investment indicators NVP method at risk was considered worthy, in which investment opportunities with decent enough small and big profit opportunities.Key words: banana, financial analysis, NVP at risk, tissue culture